Geometric interpretation of quadratic centers - Gaiko, V.A. (Нелінійні коливання, 2003)
Polynomial differential equations are considered. We apply Erugin’s two-isocline method for the global
qualitative analysis of such equations and give a geometric interpretation of the quadratic centers. Розглянуто полiномiальнi диференцiальнi рiвняння. Для глобального якiсного аналiзу таких
рiвнянь застосовано двоiзоклiнний метод Єругiна. Наведено геометричну iнтерпретацiю квадратичних центрiв.